2021
DOI: 10.1177/1120672121992984
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of macular microvasculature and retinal layers alterations in patients with macula off retinal detachment after vitrectomy

Abstract: Purpose: To examine the changes in retinal microvasculature in association with retinal layers’ condition in patients with rhegmatogenous retinal detachment (RRD) treated with pars plana vitrectomy (PPV). Methods: Participants in this study were 89 patients with macula off RRD, who were successfully treated with PPV and gas tamponade without internal limiting membrane peeling, in two centers. All participants underwent best corrected visual acuity (BCVA) measurement, slit-lamp examination, fundoscopy, spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…The fellow eye was used as a control. It is true that the SCP FAZ in the RRD group was greater than that in the control group, i.e., different than in our study, but the differences were not statistically significant ( p > 0.05) [ 44 ].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The fellow eye was used as a control. It is true that the SCP FAZ in the RRD group was greater than that in the control group, i.e., different than in our study, but the differences were not statistically significant ( p > 0.05) [ 44 ].…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, Christou et al [ 44 ] showed a lower VD in SCPs among 23 RRD patients who underwent PPV and applied gas endotamponade compared to the control. The fellow eye was used as a control.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies including 430 RRD eyes and 430 control eyes were selected in this study ( Agarwal et al, 2019 ; Woo et al, 2018 ; McKay et al, 2020 ; Ng et al, 2020 ; Wang et al, 2019 ; Hong et al, 2020 ; Bonfiglio et al, 2020 ; Barca et al, 2020 ; Christou et al, 2021 ; Liu et al, 2021 ; D'Aloisio et al, 2022 ; Chatziralli et al, 2022 ), as indicated in Table 1 . The search strategy for Pubmed is showed in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%